2012
DOI: 10.1007/s12263-011-0278-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of lipogenic genes may contribute to hyperglycemia and alterations in plasma lipids in response to dietary iron deficiency

Abstract: Iron deficiency (ID) remains a public health concern affecting ~25% of the world's population. Metabolic consequences of ID include elevated plasma glucose concentrations consistent with increased reliance on glucose as a metabolic substrate, though the mechanisms controlling these responses remain unclear. To further characterize the metabolic response to ID, weanling male Sprague-Dawley rats were fed either a control (C; 40 mg Fe/kg diet) or iron-deficient (ID; 3 mg Fe/kg diet) diet or were pair-fed (PF) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 54 publications
4
35
0
Order By: Relevance
“…Furthermore, the deletion of Hamp1 alleles did not alter their basic expression levels. Iron-deficient rodents have been reported to display elevated lipogenic gene expression, which indirectly supports our findings [55][56][57] . Hepatic lipid homeostasis is also regulated by lipid export via VLDL secretion.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the deletion of Hamp1 alleles did not alter their basic expression levels. Iron-deficient rodents have been reported to display elevated lipogenic gene expression, which indirectly supports our findings [55][56][57] . Hepatic lipid homeostasis is also regulated by lipid export via VLDL secretion.…”
Section: Discussionsupporting
confidence: 89%
“…An independent study recently confirmed these findings, showing enhanced expression of lipogenic genes and alterations in levels of plasma lipids in response to dietary iron deficiency (52). The precise mechanisms responsible for the relative hyperglycemia associated with ferropenic anemia remain unclear (53,54).…”
Section: The Paradox Of Iron Deficiencymentioning
confidence: 87%
“…In rats, Fe deficiency reduced β-oxidation of fatty acids, allowing the fatty acids to be diverted towards TG synthesis (Bartholmey and Sherman, 1985). Davis et al (2012) also reported that Fe deficiency reduced gene expression related to hepatic β-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chen et al (2016) found that higher concentration of Fe exposure tended to reduce the lipogenic enzymatic activity and gene expression (G6PD and FAS). In rats, Davis et al (2012) reported that Fe deficiency increased hepatic lipogenesis by up-regulating gene expression related to lipogenesis. Our study indicated that the reduced FAS activity was attributable to the reduction in its mRNA expression, suggesting that FAS was regulated by Fe mainly at the transcriptional level, similar to the study by Chen et al (2016).…”
Section: Discussionmentioning
confidence: 99%